THE INFLUENCE OF SCRABBLE GAME IN TEACHING VOCABULARY MASTERY AT TENTH GRADE STUDENTS OF SMKN 7 PANDEGLANG - Diaz Puri Ryandita; Isti Pristiyani Kusumawati (PROJECT (Professional Journal of English Education), 2019)
This study is aimed to investigate the influence of scrabble game in teaching vocabulary mastery at tenth grade students of SMKN 7 Pandeglang. This research used randomized matched subject pretest posttest design control group.Seventy students were appointed as the representative sample of this research. Samples were taken by considering students’ English score. The resulted data analyzed and compared by using comparison technique, whether the researcher compared the results of pre-test and post-test of both different groups, average score pretest and posttest of accountancy class (did not use scrabble) is 41.74285714 average score pretest and posttest is 49.37142857 (use scrabble game). Based on analysis of data, this research showed that students who are taught by using scrabble game got higher score than students who are taught without any teaching technique.Keywords:        Teaching Vocabulary Mastery, Teaching Vocabulary’s Game, and Scrabble Game